ANALYTIC HIERARCHY PROCESS FOR DETERMINATION OF DECISION MAKING IN THE SELECTION OF CONTRACTORS - Iman Nurjaman; Rully Andika Listyantoko (Industry Xplore, 2023)
Decision making at top management is a strategic issue, this affects and becomes one of the determining factors for success for the company. The selection of contractors is one way to make decisions, the method that is widely used in decision making is the Analytic Hierarchy Process (AHP) method, although this method is very old, this method is still widely used, because AHP is one of the popular decision-making methods for decision making. multi-criteria (MCDM), by taking a case study in a well-known palm oil company headquartered in Jakarta (Indonesia). The results of the criteria score are consistent with 0.002 and in the final selection of the first ranked alternative there are 3 (three) contractors with the best score of 25% who excel in Pre-Qualification and Commercial Criteria testing, with this method the company is expected to be able to choose the right contractor for business partners and smooth operations.